Bhinneka Tunggal Ika and Bahasa Daerah: Challenges in the Present and Future - Candria, Mytha; Wulandari, Dwi (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
The reason underlying the writing of this paper concerns the policies of Indonesian government that favoured unity over diversity, which impacted, among others, the number of local languages in Indonesia. Because of the previous government policies, Indonesia is currently facing a challenging situation, in which more than 400 of its local languages are endangered and extinct. The policies were against the spirits of Indonesian official motto Bhinneka Tunggal Ika , which values both unity and diversity. This means that Bhinneka Tunggal Ika acknowledges the centrality of both the national language and local languages. Thus, both languages need to be preserved and supported if Indonesians are to actualize the spirits of Bhinneka Tunggal Ika , meaning unity in diversity  and diversity in unity .